Pediatric eosinophilic esophagitis: a review for the clinician - Simona Barni; Stefania Arasi; Carla Mastrorilli; Luca Pecoraro; Mattia Giovannini; Francesca Mori; Lucia Liotti; Francesca Saretta; Riccardo Castagnoli; Lucia Caminiti; Antonella Cianferoni; Elio Novembre (BMC, 2021)
Abstract Eosinophilic esophagitis (EoE) is a chronic clinical-pathologic disease characterized by eosinophilic infiltration of the esophageal epithelium with esophageal dysfunction symptoms. EoE can occur at any age and has different clinical manifestations depending on the age onset. To date, esophago-gastroduodenal endoscopy (EGD) with biopsy is the gold-standard for EoE diagnosis. According to the recent consensus guidelines, proton pump inhibitors, corticosteroids and elimination diets could be a first-line therapy option. The aim of the treatment is clinical and histological remission for preventing long-lasting untreatable fibrosis. A multidisciplinary approach (allergist, gastroenterology, dietitian, and pathologist) is recommended for managing patients affected by EoE, given the complexity of its treatment. This review will provide a practical guide to assist pediatricians treating children with EoE. Moreover, it highlights the unmet needs in diagnosis and treatment that require urgent attention from the scientific community in the aim of improving the management of patients with EoE.